Maximizing Healthcare Service Information System: Understanding the Influence of Integration on Efficiency - Kuswari, Mury; Gantino, Rilla; Maratis, Jerry (ADI Publisher, 2025)
The increasing complexity of healthcare systems, rising service demand, and the importance of information technology in enhancing accessibility and service quality highlight the need for effective solutions. This study aims to explore how the integration of information systems in healthcare services can influence operational efficiency. The research involves comprehensive analysis of relevant literature, case studies, and interviews with experts in the healthcare industry. The findings reveal that integrated healthcare information systems improved operational efficiency by 35%, reduced data duplication by 25, and decreased patient wait times by an average of 40. The study also examines how integration optimizes administrative processes, patient data management, and coordination among service units. The integration of healthcare information systems in healthcare services offers significant benefits in enhancing operational efficiency, improving patient experiences, and raising overall service quality. Therefore, prioritizing investment and development in integrated information systems is critical to improving healthcare system performance.